2006
DOI: 10.1021/bi052505d
|View full text |Cite
|
Sign up to set email alerts
|

Translational Fidelity Mutations in 18S rRNA Affect the Catalytic Activity of Ribosomes and the Oxidative Balance of Yeast Cells

Abstract: The function of mutations rdn1A, rdn1T, and rdn2 in 18S rRNA of Saccharomyces cerevisiae is investigated. The mutations correspond to substitutions C1054A, C1054U in helix 34, and G517A in helix 18 of 16S rRNA in Escherichia coli, respectively, in which the first and third mutations caused nonsense suppression, while C1054U caused no suppression. In yeast, rdn1A caused phenotypic suppression at nonsense codons, whereas rdn1T and rdn2 caused antisuppression. We provide in vitro evidence that, in addition, rdn1A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The reasons why post-diauxic culture cells show a greater resistance to hydrogen peroxide when containing a larger amount of assembled ribosome 1 are unclear, but may indicate that control of the protein biosynthesis machinery is important for the oxidative equilibrium of the cell, in agreement with recent data showing that changes in translational fidelity affect this balance. 48 In conclusion, the recent characterization of the CARA strain strongly supports the emerging concept that Pol I activity is a key element for the coordinated synthesis of ribosome components. To dissect the molecular mechanisms involved, and more specifically to understand how the level of Pol I transcription impacts on Pol II transcription will certainly represent a major breakthrough.…”
Section: What Are the Consequences Of Ribosome Biogenesis Deregulation?supporting
confidence: 55%
“…The reasons why post-diauxic culture cells show a greater resistance to hydrogen peroxide when containing a larger amount of assembled ribosome 1 are unclear, but may indicate that control of the protein biosynthesis machinery is important for the oxidative equilibrium of the cell, in agreement with recent data showing that changes in translational fidelity affect this balance. 48 In conclusion, the recent characterization of the CARA strain strongly supports the emerging concept that Pol I activity is a key element for the coordinated synthesis of ribosome components. To dissect the molecular mechanisms involved, and more specifically to understand how the level of Pol I transcription impacts on Pol II transcription will certainly represent a major breakthrough.…”
Section: What Are the Consequences Of Ribosome Biogenesis Deregulation?supporting
confidence: 55%
“…Few mutations may be sufficient to alter the fidelity of a ribosome, for example, a single mutation in the S5 ribosomal protein in E. coli increases frameshifting and nonsense mutations [ 38 ]. In yeast, mutations in the 18S RNA have been found that both increase and decrease translational fidelity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This helix has also been implicated in decoding in both the A and P sites during elongation and initiation, respectively, and in the translocation of mRNA and tRNAs through the ribosome (O'Connor et al 1997;Matassova et al 2001;Konstantinidis et al 2006). Given the importance of the flexibility of this region in allowing conformational changes during each of these processes, it seems possible that yeIF4B binding could induce a rearrangement in h34 that promotes mRNA recruitment.…”
Section: Yeif4b Is a 40s Ribosomal Subunit-binding Proteinmentioning
confidence: 99%